Diseases pattern in the department of physical medicine & rehabilitation in a tertiary level hospital - Hossain, Md Shahadat; Chakraborty, Prasanta Kumar; Rahman, Sohely; Islam, Md Jahidul; Amin, Md Ruhul; Saha, Ripon Kumer; Khan, Moinuddin Hossain; Yasmin, Nahid (Bangladesh Medical Journal, 2016)
This is a retrospective study carried out at the department of Physical Medicine and Rehabilitation in Dhaka Medical College Hospital (DMCH), Dhaka for the period of one year from 1st January, 2012 to 31st December, 2012. The purpose of the study was to observe the disease pattern and demographic characteristics of patients attending the department of Physical Medicine and Rehabilitation in a tertiary care hospital. Total sixteen thousand two hundred ninety seven (n=16297) patients were studied, of which 48% were male and 52% were female. The mean age was 43.64 ± 5.12 years, maximum patients (27.96%) belong to 41-50 years of age. Maximum patients (51%) were come from Dhaka city and most of the studied patients were housewife (36.73%). Largest disease group was non-specific low back 130 pain (16.42%). Regarding disease pattern, 44.07% of patients rheumatological, 17.25% neurological, 25.11% orthopaedic condition. Among leading diseases, 16.77% were non-specific low back pain, 10.13% osteoarthritis of knee joints, 8.15% stroke, 7.56% lumbar spondylosis, 7.05% cervical spondylosis, 6.43% adhesive Capsulitis, 3.84% neck sprain/strain 3.57% Facial palsy, 3.18% fibromyalgia and 3.12% tennis elbow. Bangladesh Med J. 2014 Sep; 43 (3): 130-133